Is there a need for a hospital based smoking cessation programme in Malaysia? - Robson, N.Z.; Mohammad Hussain, H. (2008)
Smoking cessation programmes have been available for almost 2 decades in Malaysia. However the programmes have mainly focussed on outpatient primary care settings. More attention is needed to address and treat smokers presenting to hospitals with acute and chronic medical illness as hospitals provide good settings to implement smoking cessation intervention. For instance, a tobacco related medical illness may boosts a smoker's motivation to stop, especially when the smoker perceives smoking as the cause of his illness and understands the gains achieved by smoking cessation. Besides bringing a smoker in contact with health personnel who may offer assistance to a smoker to help him stop smoking, a hospital stay also provide an opportunity for the health carer to initiate and practice the government policy of no smoking in the hospitals. This article addresses the importance of having a hospital-based smoking cessation programme for the Malaysian hospitals.